Unilateral laminotomy with bilateral spinal canal decompression: systematic review of outcomes and complications - Algarni, Nizar; Al-Amoodi, Mohamed; Marwan, Yousef; Bokhari, Rakan; Addar, Abdullah; Alshammari, Abdullah; Alaseem, Abdulrahman; Albishi, Waleed; Alshaygy, Ibrahim; Alabdullatif, Fahad (BMC musculoskeletal disorders, 2023)
Background Unilateral laminotomy with bilateral spinal canal decompression has gained popularity recently. Aim To systematically review the literature of unilateral laminotomy with bilateral spinal canal decompression for lumbar spinal stenosis (LSS) aiming to assess outcomes and complications of the different techniques described in literature. Methods On August 7, 2022, Pubmed and EMBASE were searched by 2 reviewers independently, and all the relevant studies published up to date were considered based on predetermined inclusion and exclusion criteria. The subject headings “unilateral laminotomy”, “bilateral decompression” and their related key terms were used. The Preferred Reporting Item for Systematic Reviews and Meta-Analyses statement was used to screen the articles. Results A total of seven studies including 371 patients were included. The mean age of the patients was 69.0 years (range: 55–83 years). The follow up duration ranged from 1 to 3 years. Rate of postoperative pain and functional improvement was favorable based on VAS, JOA, JOABPEQ, RMDW, ODI and SF-36, for example improved from a range of 4.2–7.5 preoperatively on the VAS score to a range of 1.4–3.0 postoperatively at the final follow up. Insufficient decompression was noted in 3% of the reported cases. The overall complication rate was reported at 18–20%, with dural tear at 3.6–9% and hematoma at 0–4%. Conclusion Unilateral laminotomy with bilateral decompression has favorable short- and mid-term pain and functional outcomes with low recurrence and complication rates. This, however, needs to be further confirmed in larger, long-term follow-up, prospective, comparative studies between open, and minimally invasive techniques.